## Chapter 1 Integers Exercise 1.2

**Question 1: Write down a pair of integers whose:(a) sum is -7Answer:**

= -7 + 0

= -7

**(b) difference is – 10**

Answer:

Answer:

= -25 - (-15)

= – 25 + 15

= -10

**(c) sum is 0**

Answer:

Answer:

= 4 + (-4)

= 4 - 4

= 0

**Question 2: (a) Write a pair of negative integers whose difference gives 8**

Answer:

Answer:

= (-5) - (- 13)

= -5 + 13

= 8

**(b) Write a negative integer and a positive integer whose sum is – 5.**

Answer:

Answer:

= -25 + 20

= -5

(c) Write a negative integer and a positive integer whose difference is – 3.

Answer:

(c) Write a negative integer and a positive integer whose difference is – 3.

Answer:

= -6 - (-3)

= -6 + 3

= -3

Question 3: In a quiz, team A scored – 40, 10, 0 and team B scored 10, 0, – 40 in three successive rounds. Which team scored more? Can we say that we can add integers in any order?

Answer:

Question 3: In a quiz, team A scored – 40, 10, 0 and team B scored 10, 0, – 40 in three successive rounds. Which team scored more? Can we say that we can add integers in any order?

Answer:

Score of team A = -40, 10, 0

Score of team B = 10, 0, -40

Total score obtained by team A = ?

Total score obtained by team B = ?

Team A score = -40 + 10 + 0

= -30

Team B score = 10 + 0 + -40

= -30

Therefore, the score of the both A team and B team is same. Yes, we can say that we can add integers in any order.

**Question 4: Fill in the blanks to make the following statements true:**

(i) (-5) + (-8) = (-8) + (_)

Answer:

(i) (-5) + (-8) = (-8) + (_)

Answer:

Let the unknown integer be x.

= (-5) + (-8) = (-8) + (x)

= -5 - 8 = -8 + x

= -13 = -8 + x

= -13 + 8 = x

= x = -5

**(ii) –53 + _ = –53**

Answer:

Answer:

Let unknown integer be x.

= -53 + x = -53

= x = -53 + 53

= x = 0

**(iii) 17 + _ = 0**

Answer:

Answer:

Let unknown integer be x.

= 17 + x = 0

= x = 0 – 17

= x = – 17

**(iv) [13 + (– 12)] + (_) = 13 + [(–12) + (–7)]**

Answer:

Answer:

Let the unknown integer be x.

= [13 + (-12)] + (x) = 13 + [(-12) + (-7)]

= [13 - 12] + (x) = 13 + [-12 - 7]

= [1] + (x) = 13 + [-19]

= 1 + (x) = 13 - 19

= 1 + (x) = -6

= x = -6 - 1

= x = -7

**(v) (– 4) + [15 + (–3)] = [– 4 + 15] + _**

Answer:

Answer:

Let the unknown integer be x.

= (-4) + [15 + (-3)] = [- 4 + 15] + x

= (-4) + [15 - 3)] = [- 4 + 15] + x

= (-4) + [12] = [11] + x

= 8 = 11 + x

= 8 - 11 = x

= x = -3

## No comments:

## Post a Comment